The Implementation of Optofluidic Microscopy on a Chip Scale and Its Potential Applications in Biology - Lee, Lap Man (California Institute of Technology, 2012)
This thesis presents an effort to miniaturize conventional optical microscopy to a chip level using microfluidic technology. Modern compound microscopes use a set of bulk glass lenses to form magnified images from biological objects. This limits the possibility of shrinking the size of a microscope system. The invention of micro/nanofabrication technology gives hope to engineers who want to rethink the way we build optical microscopes. This advancement can fundamentally reform the way clinicians and biologists conduct microscopy. Optofluidic microscopy (OFM) is a miniaturized optical imaging method which utilizes a microfluidic flow to deliver biological samples across a 1-D or 2-D array of sampling points defined in a microfluidic channel for optical scanning. The optical information of these sampling points is collected by a CMOS imaging sensor on the bottom of the microfluidic channel. Although the size of the OFM device is as small as a US dime, it can render high resolution images of less than 1 μm with quality comparable to that of a bulky, standard optical microscope. OFM has a good potential in various biological applications. For example, the integration of an OFM system with high-speed hydrodynamic focusing technology will allow very large scale imaging-based analysis of cells or microorganisms; the compactness and low cost nature of OFM systems can enable portable or even disposable biomedical diagnostic tools for future telemedicine and personalized health care.
Keywords: Optical Imaging; Microfluidics; Electrokinetics; Optofluidics; Bioengineering; Lab-on-a-chip; Biomedical Microdevices